Appraisal of the Role of Law Clinics in Internally Displaced Persons and Refugee Camps in Nigeria. (July 2019) - Abdulkadir, Maryam Idris
The crises from the northeastern part of Nigeria and neighbouring countries especially around the Lake Chad region (Cameroun and Chad) have created a lot of internally displaced persons (IDPs) and refugees in the country. This has led to creation of such camps that are scattered all over the country, that is, in the North East, South, South East and the Federal Capital Territory, Abuja. A lot of humanitarian crises occur in such camps, the most disturbing of which is a violation of certain fundamental human rights, like right to liberty and right to dignity, exploitation and sexual assault. This has led to the creation of Refugee and IDP camps. This article examined the role that law clinics can play in addressing the legal issues highlighted. The history and development of legal education in Nigeria and how it gave birth to law clinics was traced. Moreover, the causes of creation of refugee and IDP camps were discussed. The article recommends that law clinics, through social justice, access to justice and client interview, can play a tremendous role in addressing the legal problems faced by the inhabitants of the camps, and this will also help achieve one of the learning outcomes of the course which deals with humanitarian law. The article further states that the presence/role of law clinics will not only benefit the students of the law clinic and the inhabitants of the camps but also benefit the Federal Government of Nigeria through data collection and statistics from these camps, and it will be a means for the government to curtail human rights violation in such areas.